Public debt sustainability and debt dynamics: The case of Tanzania - Maureen Were; Lekinyi Mollel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Rising public debt in sub-Saharan Africa remains a matter of concern. We provide an analysis of public debt and debt sustainability in Tanzania, focusing on external debt. Though current and previous analyses using the IMF-World Bank debt sustainability framework indicate low risk of public external debt distress, these analyses are sensitive to exchange rate volatility and export shocks and are predicated on strong assumptions of robust future economic growth and reduced government borrowing. Moreover, empirical evidence of debt sustainability based on the fiscal reaction function approach is weak. The challenge lies in ensuring debt remains sustainable, given the need to scale up development expenditure to address infrastructure gaps amid dwindling donor financing and vulnerability to exogenous shocks, particularly in light of the COVID-19 pandemic. Rapid debt accumulation-particularly commercial debt-could expose Tanzania to external risks. Leveraging on concessional borrowing, efficient public investment, enhanced debt management, and domestic resource mobilization are critical.
Keywords: E60; E62; H63; H68; 330; public debt; Tanzania; debt sustainability; external debt